Leitores, literatura, ensino híbrido: reflexões sobre o ato de ler contemporâneo - Hoffmann, Adriane Ester (2020)
The theme of this thesis expatiates on literary education, and the possibility of forming literary readers in the technological, digital, and contemporary age. The central aim is develop a reading practice, in a public school of Frederico Westphalen/RS city, engaging the last grades of elementary school, starting from the literary text mixing on-site and online discussions and activities. In addition, the using of technological resources is involved in order to expose that the students are protagonists of their learning when the school promotes interactive situations. The theoretical framework, in which one is based the research, is focused on conceptions of contemporary reading and readers profile in the technological age proposed by Michèle Petit (2009, 2013), Sandra Sánchez García and Santiago Yubero (2017), Gemma Lluch (2017), Lúcia Santaella (2013, 2015), Edvaldo Souza Couto (2016), Regina Zilberman (2001, 2012, 2016), Anne-Marie Chartier and Roger Chartier (2016), Tania Mariza Kuchenbecker Rösing (2016), Regina Zilberman and Marisa Lajolo (2017), and Antonio Carlos Xavier (2012, 2013). To identify the specificities of the literary reader, I look to the contributions of Teresa Colomer (2007), Anne-Marie Chartier (2016), Tania Mariza Kuchenbecker Rösing (1999), Regina Zilberman e Marisa Lajolo (2017), Pedro Cesar Cerrillo (2016, 2017), and Martha Nussbaum (2015). The hybrid teaching is taken as one of the options that enable different ways of improvement in students learning. This conceptions comes from the investigations of Elisabete Cerutti and Arnaldo Nogaro (2016), Pierre Lévy (1999), Carla Viana Coscarelli and Ana Elisa Ribeiro (2014), Michael Horn and Heather Staker (2015), José Armando Valente (2015), José Moran (2015), César Coll and Carles Monereo (2010), José Luis Rodriguez Illera and Ana Escofet Roig (2010), and Carles Monereo and Martha Fuentes (2010). From this research, I formulate the thesis that the literary reception, developed by teachers at school, helped by technology, could support the contemporary reader formation. The research is exploratory and descriptive, developed by fieldwork, qualitative analysis, data collection tools, and application of reading practice. In the first part, which forms the diagnostic, 800 students from public schools of Frederico Westphalen city, in the last grades of elementary school, who answered a questionnaire, composed the corpus of this study. In the second part, I chose one school, among the selected in the diagnostic, and a grade to apply a reading practice. The analysis point out that the teacher interventions during the reading process and the analysis of the literary work sets different aspects of what is reading. Therefore, the reader develops more and more his interest on reading, improve his worldview and makes possible the reflection about underpinning issues on the literary learning. The analysis unravel, also, that in literary education, in the contemporaneity, is important link new ways of reading and new technological resources to constitute the learning in a collaborative practice.